When Negativity Becomes Vanity: Hegel’s Critique of Romantic Irony - Mascat, Jamila M.H. (Stasis, 2013)
Hegel, the “philosopher of negation” par excellence, took great care throughout his speculative enterprise to distinguish between opposite stances of the negative, highlighting and differentiating the multiple modes through which negativity deploys itself. And although, in the Phenomenology of Spirit, he celebrated the “tremendous power of the negative” and the constitutive function performed by negativity as the fundamental motion of being, thinking, and acting, he nonetheless developed a harsh critique of Romantic irony’s negative Stimmung1. This article, by focusing on the peculiar exercise of negativity that the philosopher attributes to Romantic irony in the Aesthetics and his “Review of Solger’s Posthumous Writings and Correspondence” (1828), investigates Hegel’s characterization of irony as vanity (Eitelkeit)2. Hegel’s critical understanding of vanity, in fact, conveys a significant political stance regarding the very concept of negation, one that warns against the apolitical retreat into both narcissism and nihilism.